2012
DOI: 10.1177/0883073812443590
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Care Indicators for Infantile Spasms

Abstract: We developed a comprehensive set of quality-of-care indicators for the management of children with infantile spasms in the United States, encompassing evaluation, diagnosis, treatment, and prevention and management of side effects and comorbidities. The indicators were developed using the RAND/UCLA Modified Delphi Method. After a focused review of the literature and guidelines by the study team, an expert panel (nominated by leaders of Child Neurology Society, American Epilepsy Society, and National Institute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 45 publications
0
9
1
Order By: Relevance
“…6 The spontaneous remission rate of infantile spasms in limited natural history studies is 25% at 12 months after the onset of infantile spasms 7 The considerable variation in the management of infantile spasms, has led to the publication of treatment surveys, consensus statements, practice parameters, and reviews of the subject. [8][9][10][11][12][13][14][15][16] A survey on the evaluation and treatment of infantile spasms among members of the Child Neurology Society reported that the majority of neurologists surveyed use adrenocorticotrophic hormone (ACTH) as the first-line treatment of infantile spasms not caused by tuberous sclerosis complex and vigabatrin as the first-line treatment of infantile spasms caused by tuberous sclerosis complex. 13 The 2004 American Academy of Neurology and Child Neurology Society practice parameter on the medical treatment of infantile spasms and the 2012 update of this evidence-based guideline concluded that ACTH or vigabatrin may be useful for the short-term treatment of infantile spasms, with ACTH being more effective than vigabatrin excluding patients with tuberous sclerosis complex.…”
Section: Introductionmentioning
confidence: 99%
“…6 The spontaneous remission rate of infantile spasms in limited natural history studies is 25% at 12 months after the onset of infantile spasms 7 The considerable variation in the management of infantile spasms, has led to the publication of treatment surveys, consensus statements, practice parameters, and reviews of the subject. [8][9][10][11][12][13][14][15][16] A survey on the evaluation and treatment of infantile spasms among members of the Child Neurology Society reported that the majority of neurologists surveyed use adrenocorticotrophic hormone (ACTH) as the first-line treatment of infantile spasms not caused by tuberous sclerosis complex and vigabatrin as the first-line treatment of infantile spasms caused by tuberous sclerosis complex. 13 The 2004 American Academy of Neurology and Child Neurology Society practice parameter on the medical treatment of infantile spasms and the 2012 update of this evidence-based guideline concluded that ACTH or vigabatrin may be useful for the short-term treatment of infantile spasms, with ACTH being more effective than vigabatrin excluding patients with tuberous sclerosis complex.…”
Section: Introductionmentioning
confidence: 99%
“…For example, evidence regarding infantile spasms is sufficient for guidelines targeted at both physicians and parents. [30][31][32][33] Most early-onset epilepsies, however, are individually rare, thus precluding the feasibility of robust randomized clinical trials needed to develop such guidelines. Recent treatment recommendations concluded that rigorous evidence-based guidelines for selecting treatments based on syndromes were not possible at this time.…”
Section: Community Resourcesmentioning
confidence: 99%
“…13,[24][25][26] Thus, consensus quality improvement guidelines strongly recommend evaluation with prolonged EEG and treatment initiation as soon as possible, certainly within 1 to 2 weeks of presentation. [27][28][29][30] Take a Step-Wise Approach to the Etiologic Investigation-Opportunity 3…”
Section: Epileptic Spasm (Es)mentioning
confidence: 99%
“…The child may demonstrate isolated forceful head bobs, facial grimace, eye rolling, eye deviation, or brief staring benefit from specialized treatment (►Table 5). 27,[29][30][31] Many speculate that brain dysfunction from essentially any cause early in life may converge into a "final common pathway" that ultimately results in the development of IS. Indeed, more than 200 conditions are known to be associated with IS.…”
Section: Subtle Spasmsmentioning
confidence: 99%